Pengolahan produk ikan lele organik yang berwawasan lingkungan - Muhammad Irfan; Andi Sukainah; Muhammad Wiharto; Diyahwati Diyahwati; Amirah Mustaring (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Partners of the Partnership Program (PKM) are students of Entrepreneurship Education in Technology. The problem is: (1) lack of knowledge about organic catfish, (2) lack of skill in making processed from catfish, (3) low level of preference for consuming catfish (4) high production of catfish. The target is for Agricultural Technology Education students who are just starting their business activities. The method used is: lectures, demonstrations, discussions, questions and answers, and counterpart partners. The results achieved were (1) participants had knowledge in organic catfish cultivation, (2) participants had skills in making processed catfish products, (3) there were innovations in catfish processed products